2020
DOI: 10.1021/jacs.9b11454
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of ISC Iron–Sulfur Cluster Biogenesis Revealed by High-Resolution Native Mass Spectrometry

Abstract: Iron−sulfur (Fe−S) clusters are ubiquitous protein cofactors that are required for many important biological processes including oxidative respiration, nitrogen fixation, and photosynthesis. Biosynthetic pathways assemble Fe-S clusters with different iron-to-sulfur stoichiometries and distribute these clusters to appropriate apoproteins. In the ISC pathway, the pyridoxal 5′phosphate-dependent cysteine desulfurase enzyme IscS provides sulfur to the scaffold protein IscU, which templates the Fe-S cluster assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 85 publications
6
70
0
Order By: Relevance
“…Interestingly, with the mouse system it was shown that in the absence of iron, the transfer of persulfide is abolished, which points to a metal-dependent process [23]. A similar iron-dependent persulfide transfer process was recently reported with the E. coli system [78]. Thus, the presence of iron is required to allow the transfer of persulfide, which experimentally confirms the iron-first model that was earlier proposed and discards the sulfur-first hypothesis (Figure 5).…”
Section: Sulfur Transfer To the Iscu/iscu Scaffold A Metal-driven Processsupporting
confidence: 81%
See 1 more Smart Citation
“…Interestingly, with the mouse system it was shown that in the absence of iron, the transfer of persulfide is abolished, which points to a metal-dependent process [23]. A similar iron-dependent persulfide transfer process was recently reported with the E. coli system [78]. Thus, the presence of iron is required to allow the transfer of persulfide, which experimentally confirms the iron-first model that was earlier proposed and discards the sulfur-first hypothesis (Figure 5).…”
Section: Sulfur Transfer To the Iscu/iscu Scaffold A Metal-driven Processsupporting
confidence: 81%
“…Titration by circular dichroism (CD) indicated that ISCU binds a single Fe 2+ ion and Mössbauer spectroscopies showed that it is a high spin Fe(II) center and confirmed the presence of several cysteines in the coordination sphere of the metal. Fe-S cluster assembly assays using the complete mouse ISC machinery with the NFS1-ISD11-ACP complex, FDX2 and FDXR show that iron-loaded ISCU (Fe-ISCU) is competent for Fe-S cluster assembly, while the zinc-loaded form (Zn-ISCU) is not, which indicates that binding of iron in the assembly site is the initial step in Fe-S cluster biosynthesis [23] Binding of iron in the assembly site was later on reported with E. coli IscU upon removal of the zinc ion, which suggests that the first step in the mechanism of Fe-S cluster synthesis is conserved [78]. Surprisingly, the investigations of iron-binding sites in IscU/ISCU proteins from E. coli, human, drosophila and yeast by X-ray absorption spectroscopy (XAS) led to the conclusion that iron does not initially bind in the assembly site but in a 6-coordinated site comprising only nitrogen and oxygen [79][80][81].…”
Section: Figurementioning
confidence: 99%
“…The ability of DJB1-noHis to potentially bind different forms of Fe-S is also observed in natural proteins, such as those involved in Fe-S cluster biosynthesis [78][79][80][81]. The Fe-S chaperone, IscU is proposed to initiate by recruiting Fe 3+ coordinated by cysteines in a loop region at the end of a helix [79], then assembling an intermediate Fe 2 S 2 cluster at the same site, and eventually converting it to an Fe 4 S 4 cluster [80,81]. The flexibility of IscU in binding the Fe-S cofactors of different stoichiometries is associated with its cysteines being located on a flexible terminal loop.…”
Section: Discussionmentioning
confidence: 91%
“…The [2Fe-2S] cluster is coordinated by Cys69, Cy95, His137 and Cys138. It has been reported another, lower affinity, iron binding site in ISCU although its role in iron–sulfur cluster biogenesis remains to be analyzed [ 12 , 13 ]. It should be mentioned that once mounted on the ISCU assembly site, the [2Fe-2S] group is transferred to other proteins.…”
Section: Introductionmentioning
confidence: 99%